Structural topology optimization with positive and negative Poisson's ratio materials. Issue 5 (25th January 2020) - Jia, Jiao; Hu, Jianxing; Wang, Yongbin; Wu, Shiqing; Long, Kai
Abstract : Purpose: Negative Poisson's ratio (NPR) material has huge potential applications in various industrial fields. However, lower Young's modulus due to the porous form limits its further applications. Based on the topology optimization technique, this paper aims to optimize the structure consisting two isotropic porous materials with positive Poisson's ratio (PPR) and NPR and void. Design/methodology/approach: Under prescribed dual-volume fraction constraints, the structural compliance is taken as the objective. Young's modulus and Poisson's ratio are, respectively, interpolated and expressed with Lamé's parameters for easier programming. Accordingly, the sensitivities can be derived through the chain rule. Several two- and three-dimensional illustrative examples are presented to demonstrate the capability and effectiveness of the proposed approach. The influences of Poisson's ratios, volume fractions and Young's moduli on the optimized results are investigated. Findings: For NPR materials having unique load responses, the resulting topologies of PPR and NPR materials have distinct material distributions in comparison of the results from two PPR materials. Furthermore, it is observed that higher structural stiffness can be achieved from the hybrid of PPR and NPR materials than that obtained from the structures made of individual constituent materials. Originality/value: A topology optimization methodology is proposed to design structures composed of PPR and NPR materials.